Structure-dependent optical properties of Au/Ag irradiated TiN thin films - Popovic, M.; Novakovic, M.; Vana, D.; Ronning, Carsten; Jugovic, D.; Rajic, V.; Noga, P. (Optical Materials, 2023)
Titanium nitride (TiN) is an attractive alternative for modern and future photonic applications, as its optical properties can be engineered over a wide spectral range. In this study, we have used sequential implantation of gold and silver ions with varying ion fluence, as well as subsequent annealing, in order to modify the optical and plasmonic properties of TiN thin films and correlated this to their structural properties. Our investigations show that the columnar structure of the TiN films is partially destroyed upon implantation, but metallic Au and Ag nanoparticles are formed. The irradiation further induces a reduction of the lattice constant as well as changes the TiN stoichiometry and grain size. From the optical point of view, the implanted films possess less metallicity with increasing Ag fluence and losses several times lower than the as-deposited film, which can be correlated with the deficiency of nitrogen and additional defects. Subsequent annealing partially recovered the destroyed columnar structure, and the films become more metallic where the optical losses are much smaller in comparison to the as-implanted situation, being comparable to those of pure Au and Ag. In this way, by varying the implantation fluence of silver ions properly while keeping the gold fluence constant, we were able to optimize experimental parameters in such a way to ensure the formation of TiN with desirable optical performances.
CRIS-Team Scopus Importer:2023-04-20
Keywords: Gold; Optical losses; Sequential implantation; Silver; Structural properties; Titanium-nitride